The development of talent management on long term road racer in peninsular Malaysia with individual performance as mediator - Syarizal Abdul Rahim (2023)
The existence of road racers is deemed to see vital in most countries. Their contributions are unlimited to bike development, job opportunity, and economic enhancement. The aim of this study is to determine the significant factors in the road racer's developmental pathway for long-term road racer development (LTRRD). This study investigates the effect of talent identification and selection, talent development, and socialization agents on long-term road racers’ development in the Malaysian motorsport context. Specifically, this study examines the mediating effect of individual performance on the relationship between talent identification and selection, talent development, and socialization agents with long-term road racers’ development. It is trusted that this study would add to the development of research in a related field. The data for this quantitative study are gathered from road racers which currently competing in Malaysian Cub Prix and data was analyzed using Smart PLS 3.0. The main objective of this study was to provide a better understanding of long-term road racer development in the Malaysian motorsports industry. To accomplish this objective, this study proposed and verified a model comprising of three independent variables, namely talent identification and selection, talent development, and socialization agent; a moderating variable, individual performance; and a dependent variable, long-term road racer development. The proposed model provided valuable findings. Talent identification and the selection and talent development were found to be positive significant predictors of long-term road racer development. In contrast, socialization agent was found to be a negative significant predictor of long-term road racer development. It is hoped that this study would give some insights into the development of road racer and bike industry in Malaysia.